Konsep Tanggung Jawab Negara Terhadap Kewajiban Melindungi Data Pribadi Masyarakat di Indonesia (Studi Kasus Kebocoran Data NPWP Masyarakat Indonesia) - Marshella Cenyvesta; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
This research explores the criteria and standard This study examines the importance of personal data protection in Indonesia within the rapidly evolving digital era. Personal data, such as information contained in Taxpayer Identification Numbers, holds significant economic value and may be misused if it falls into irresponsible hands. While personal data plays a vital role in business strategies and the improvement of products or services, the risk of data misuse—whether on the black market or through fraudulent activities—highlights the urgency of stricter protection measures. Since the implementation of the Automatic Exchange of Information (AEoI) system in 2018, Indonesia has committed to automatically exchanging taxpayer information with other countries to enhance tax transparency and reduce tax evasion. This research adopts a normative legal research methodology and aims to provide solutions for addressing the challenges of personal data protection in an increasingly complex digital landscape. Despite existing regulations, there remains a lack of adequate provisions specifically addressing the protection of taxpayers’ personal data in international information exchange processes. This study seeks to analyze the concept of state responsibility in safeguarding citizens' personal data and to promote the development of stronger policies regarding personal data protection in Indonesia. s essential to ensure that the use of Artificial Intelligence in Indonesia occurs ethically and responsibly. Identifying transparency, accountability, fairness, and data security and privacy as key pillars, the research underscores the importance of integrating ethical principles in all Artificial Intelligence development and deployment phases. Using a normative type of research by analyzing the existing legal and ethical framework and through legislative and comparative approaches, this research provides recommendations for strengthening AI regulations in Indonesia, thereby minimizing the risk of loss and increasing public trust in this technology.